"Harmony and Symmetry". European Society for Astronomy in Culture (SEAC) 26, Graz 27th August–1st September 2018. (23rd April 2019) - Zotti, Georg
Abstract : "Harmony and Symmetry". European Society for Astronomy in Culture (SEAC) 26, Graz 27th August–1st September 2018